Hydrogen Production from Natural Gas Using an Iron‐Based Chemical Looping Technology: Process Modeling, Heat Integration, and Exergy Analysis. Issue 8 (4th July 2019) - Kong, Fanhe; Li, Chunyi; Zhang, Yitao; Gu, Yu; Kathe, Mandar; Fan, Liang-Shih; Tong, Andrew
Abstract : H2 production under a carbon‐constrained scenario attracts intensive research focus. Currently, the state‐of‐art H2 production technology with CO2 capture is the steam‐methane reforming (SMR) process with downstream CO2 sequestration. However, the need for combusting additional natural gas to supplement the endothermic heat for the reformer and the complexity of downstream H2 purification and CO2 separation processes make SMR less efficient and economical. As an alternative, an iron‐based three‐reactor chemical looping technology to convert natural gas to H2 (NTH) with 90% CO2 capture was designed and the process modeling was presented in previous publications. This work continues the study by focusing on the heat integration and exergy analysis of the process using ASPEN PLUS and ASPEN Energy Analyzer as simulation tools. Parametric studies of varying operating parameters are conducted, and the heat exchanger network of the NTH process is designed. Finally, the performance of the NTH process is compared with SMR, showing a 4.3% (percentage point) increase in the exergy efficiency. Abstract : A chemical looping‐based natural gas to hydrogen conversion process is modeled using ASPEN Plus. The process of heat integration is performed using the ASPEN Energy Analyzer. Parametric studies are conducted to identify a feasible operating range. The study shows that the chemical looping process can significantly improve the energy and exergy efficiencies compared with conventional steam methane reforming.